Jeffrey A. Brown. The Modern Superhero in Film and Television: Popular Genre and American Culture. New York: Routledge, 2016. - Danielle A Orozco (Studies in 20th & 21st Century Literature, 2017)
Review of Jeffrey A. Brown. The Modern Superhero in Film and Television: Popular Genre and American Culture. New York: Routledge, 2016.
Keywords: Superheroes; pop culture; media studies; film; television